Distinct Responses of the Nitrogen-Fixing Marine Cyanobacterium Trichodesmium to a Thermally Variable Environment as a Function of Phosphorus Availability - Qu, Pingping; Fu, Fei-Xue; Kling, Joshua D.; Huh, Megan; Wang, Xinwei; Hutchins, David A. (Frontiers in Microbiology, 2019)
Environmental variability in the ocean is projected to be greater in the future, potentially interacting with other climate change factors like warming and changing nutrient supplies. To explore these multiple stressor relationships, we tested the influence of thermal variation on the key marine diazotrophic cyanobacterium Trichodesmium erythraeum GBRTRLI101 as a function of the limiting nutrient phosphorus (P). Two constant temperature treatments represented current winter (22°C) and summer (30°C) mean values. Three variable temperature treatments fluctuated around the constant control values: Mean 22 °C, either  2 °C or  4°C; and mean 30°C  2°C. Each thermal treatment was grown under both P-replete (10 μmol/L) and P-limiting conditions (0.2 μmol/L). Effects of thermal variability on Trichodesmium were mainly found in the two winter variable temperature treatments (22°C  2°C or  4°C). P availability affected growth and physiology in all treatments and had significant interactions with temperature. P-replete cultures had higher growth and nitrogen and carbon fixation rates in the 22°C constant control, than in the corresponding variable treatments. However, physiological rates were not different in the P-replete constant and variable treatments at 30°C. In contrast, in P-limited cultures an advantage of constant temperature over variable temperature was not apparent. Phosphorus use efficiencies (PUE, mol N or C fixed . hour-1 . mol cellular P-1) for nitrogen and carbon fixation were significantly elevated under P-limited conditions, and increased with temperature from 22°C to 30°C, implying a potential advantage in a future warmer, P-limited environment. Taken together, these results imply that future increasing temperature and greater thermal variability could have significant feedback interactions with the projected intensification of P-limitation of marine N2-fixing cyanobacteria.